Longer and warmer prewinter periods reduce post‐winter fitness in a diapausing insect. (31st March 2022) - Nielsen, Matthew E.; Lehmann, Philipp; Gotthard, Karl
Abstract: Diapause is considered an important adaptation for survival of winter; however, insects often enter diapause long before its onset. Thus, diapausing insects must also be able to survive these prewinter conditions which warm temperatures could make quite energetically taxing despite relative inactivity. We tested for both immediate and delayed fitness effects of prewinter conditions in diapausing Pieris napi butterfly pupae, experimentally exposing them to different prewinter treatments in a factorial design. We placed diapausing pupae at one of three temperatures (15, 20 and 25°C) for 1 to 16 weeks, followed by the same standardized winter for all individuals. We monitored survival of pupae at multiple points during the experiment, including after winter, as well as their change in mass. For a subset of individuals, we also made repeated metabolic measurements. We found substantial weight loss during prewinter warm periods, greater during longer prewinter treatments at higher temperatures. This weight loss was associated with elevated metabolic rates at higher temperatures which increased over the duration of the prewinter treatment. Although we found little prewinter mortality associated with these conditions, mortality was much greater post‐winter for individuals in long, warm prewinter treatments and the dry mass of adults that did survive these conditions was lower, highlighting the need to understand chronic or delayed effects of stress on fitness. Ultimately, we found substantial fitness consequences of prewinter conditions for a diapausing insect. Given that climate change will make these prewinter periods both longer and more intense, it will be important to understand how dormant organisms tolerate or reduce the length of these dormant, inactive periods. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.